Aid for Trade Building On Progress Today for Tomorrow's Future - Wilson, John S. (The World Bank, 2010)
Since 2005, donors and development agencies have increased the overall value of aid for trade and put in place several mechanisms to channel such aid and to ensure that it targets national priorities. This paper reviews recent trends in the allocation of aid for trade and analyses of its effectiveness. It identifies a number of opportunities for concerted action to enhance the impact of aid for trade initiatives, including greater involvement by middle-income countries in the initiative (through improved market access, investment flows, and knowledge transfers); deeper engagement with the private sector - a key source of information on what works and what does not; a stronger focus on improving the "behind the border" policies that affect the efficiency of key services sectors and help determine firm-level competitiveness; and a stronger focus on monitoring and evaluation of results